Monitoring and Evaluation of Fish Passage Effectiveness in Nature-like Fishway of Sanghe River Secondary Hydropower Station - SHEN Chun-ying, WANG Jing-chao, QIN Xin, CHEN Yu-bin, XUE Ru-zhan (长江科学院院报)
[Objective] With the continuous expansion of China’s water conservancy infrastructure, hydraulic structures such as dams and sluice gates have obstructed fish migration routes and altered hydrological regimes both upstream and downstream. These changes have led to fragmentation of fish habitats, population declines, and even pushed some endemic fish species to the brink of extinction. To protect aquatic biodiversity and restore river connectivity, fishways have been widely implemented as critical passage facilities. Post-construction monitoring of fishway effectiveness is essential for verifying performance and identifying potential design improvements to enhance functionality and operational management. [Methods] This study evaluated the performance of the nature-like fishway at Sanghe River Secondary Hydropower Station through comprehensive monitoring. Hydrodynamic conditions were assessed using an Acoustic Doppler Current Profiler (ADCP) and 3D acoustic Doppler velocimeter (ADV) to measure water depth, temperature, and velocity parameters, ensuring they met fish passage requirements. Fish passage was monitored using infrared underwater video surveillance and capture methods during periodic dewatering, with data collected on species composition, abundance, size distribution, and movement patterns, providing references for domestic studies on nature-like fishway construction and fish passage monitoring. [Results] Results indicated all hydrodynamic parameters met design specifications. During monitoring, reservoir levels remained stable at 75 m, with fishway depths fluctuating between 0.03-1.22 m. Average velocities were 0.79 m/s in boulder crevices and 0.635 m/s in main channels, creating suitable migratory conditions. A total of 3 954 fish from 24 species (9 orders, 14 families) were recorded, dominated by Cypriniformes (75.99%). The most abundant species were Crossocheilus reticulatus, followed by Sikukia flavicaudata and Hampala macrolepidota, with most fish measuring 10-20 cm in length and 0-5 cm in width. Migration patterns showed distinct temporal variations: 68% of fish moved upstream, with significantly greater passage efficiency during daylight hours (06:00-18:00). Peak migration occurred in July-August, validating the design assumption of April-August being the primary migration season. [Conclusions] Measures to improve fish passage effectiveness include optimizing power generation-fishway coordination, removing debris in front of dam,dredging and maintaining fishway, and regular cleaning of monitoring equipment to improve reliability. The nature-like fishway at Sanghe River has successfully reestablished connectivity and created favorable hydrodynamic conditions for fish migration, demonstrating significant conservation value for the basin’s ichthyofauna.